Do Children’s Health Resources Differ According to Preschool Physical Activity Programmes and Parental Behaviour? A Mixed Methods Study - Sterdt, Elena (MDPI, 2014)
Preschool can have positive effects on the development of a healthy lifestyle. The present study analysed to what extent different conditions, structures and behavioural models in preschool and family—children’s central social microsystems—can lead to differences in children’s health resources. Using a cross-sectional mixed methods approach, contrast analyses of “preschools with systematic physical activity programmes” versus “preschools without physical activity programmes” were conducted to assess the extent to which children’s physical activity, quality of life and social behaviour differ between preschools with systematic and preschools without physical activity programmes. Differences in children’s physical activity according to parental behaviour were likewise assessed. Data on child-related outcomes and parent-related factors were collected via parent questionnaires and child interviews. A qualitative focused ethnographic study was performed to obtain deeper insight into the quantitative survey data. Two hundred and twenty seven (227) children were interviewed at 21 preschools with systematic physical activity programmes, and 190 at 25 preschools without physical activity programmes. There was no significant difference in children’s physical activity levels between the two preschool types (p = 0.709). However, the qualitative data showed differences in the design and quality of programmes to promote children’s physical activity. Data triangulation revealed a strong influence of parental behaviour. The triangulation of methods provided comprehensive insight into the nature and extent of physical activity programmes in preschools and made it possible to capture the associations between systematic physical activity promotion and children’s health resources in a differential manner.